Design of a 100W PV based power supply for lead acid battery charging with MPPT circuit - Erping (2015)
The aim for the Final Year Project is to research and design a 100W photovoltaic based power supply using a suitable converter topology to charge a Lead acid Battery. A Maximum Power Point Tracker (MPPT) will be used to track on the maximum result from the photovoltaic characteristic by comparison of the voltage and the current to overcome the variable voltage given out by the output of the photovoltaic cell. Tracking the Maximum Power Point given by the Photovoltaic is essential since it would be desirable to charge up the Lead acid battery with the greatest amount of efficiency. Therefore, this paper would focus on the boosting capability of the DC-DC converter with the fluctuating power from the Photovoltaic to achieve this goal. In this paper, modelling will be created within the PSIM software in order to simulate the circuitry design and the behavioral characteristics of the relationship between the Photovoltaic, the DC-DC converter as well as the MPPT towards the inconsistent power supplied by the Photovoltaic. Modelling of each component namely the Photovoltaic cell, DC-DC Converter, MPPT Circuit and Battery Charging circuit are being done all through the PSIM software and are simulated to provide the results of the findings given the variables involved. All modelling circuit and component sizing are calculated through project research which would be reflected within this paper to produce the resulting to be compared respectively. Different DC-DC converter topology were explored in other similar projects to make comparison of the result, however in this paper, the Boost, Buck and SEPIC converter will be utilized to overcome this inconsistent voltage due to the Photovoltaic. Furthermore, a comparison result will also be made between converters with respect to the MPPT circuit and with converter only. The resulting converter shall then be used to charge a lead acid Battery with its respective calculation in place for higher efficiency of the system.